Trans-regional rice supply paradigm reveals unsustainable water use in China - Liang Wu (IWA Publishing, 2021)
Rice is an important staple food for more than half of the global population and one of the largest water consumers on earth. Improving the efficiency of water embedded in rice production and supply could have great implications for food and water security. This study starts from Yunnan, a traditional rice producing and consuming province in southwest China, and analyses its rice supply structure and dynamics, together with embedded water footprints (WFs) of three other regions: Northeast China, South and Southwest China and Southeast Asia. The results show that Yunnan has been through drastic food change in the past decades, leading to an increasing production and supply gap. Yunnan is found to have the least WF (778.2 m3/t) for rice production across the study regions, while Northeast China consumes the highest blue WF (364.6 m3/t) and blue to total WF ratio (97.7%). The study indicates that Northeast China is at risk of groundwater deficit due to rice production and export and the current rice production and consumption pattern is inefficient. The study suggests that policies for groundwater extraction, water resource price and international trade need to be in place to ensure sustainable food supply and water use at regional and national levels. Highlights Yunnan's rice supply and its water footprint from different transboundary regions are analyzed from the food-water nexus perspective.; Rice supply in Yunnan is found to have a cascading effect on water security in Northeast China, and the current rice supply paradigm could be both unsustainable and inefficient for water use.; This study shows the incremental needs to manage groundwater use and adjust the trading policy in China.;